The Role of Mobile Phone and Internet Use in the Performance of Rural Non-Farm Enterprises: An Analysis of Indonesian Rural Households - Binarlyn Indri Rahayu; Riyanto Riyanto (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
Rural non-farm enterprises have an increasingly important role in economic development in developing countries. The performance of rural non-farm enterprisess is expected to continue to improve in line with the use of telecommunications technology in their business. Such improvement resulted from the use of communication technologies such as mobile phones and internet that are able to reduce information search and expand market information. This study analyzes the role of mobile phone and internet utse in the performance of rural non-farm enterprises. By using household-level data from the Fifth Wave of the Indonesian family life survey (IFLS 5) in 2014 and applying the propensity score matching method, the study found that the use of mobile phones and the internet has a positive impact on the performance of rural non-farm household enterprisess. It shows that the telecommunications infrastructure development policy in rural areas is able to provide economic improvement for rural households.